2016
DOI: 10.1007/s12031-016-0732-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Galanin 3 Receptor Aggravates Murine Autoimmune Arthritis

Abstract: Neurogenic inflammation mediated by peptidergic sensory nerves has a crucial impact on the pathogenesis of various joint diseases. Galanin is a regulatory sensory neuropeptide, which has been shown to attenuate neurogenic inflammation, modulate neutrophil activation, and be involved in the development of adjuvant arthritis, but our current understanding about its targets and physiological importance is incomplete. Among the receptors of galanin (GAL1–3), GAL3 has been found to be the most abundantly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…In agreement with its putative role in IBD, we reported anti-inflammatory effects of GAL 3 R signaling on neutrophil-related MPO levels in murine arthritis 13 . In contrast, pro-inflammatory properties of GAL 3 R signaling were observed in murine psoriasis 14 and pancreatitis 15 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with its putative role in IBD, we reported anti-inflammatory effects of GAL 3 R signaling on neutrophil-related MPO levels in murine arthritis 13 . In contrast, pro-inflammatory properties of GAL 3 R signaling were observed in murine psoriasis 14 and pancreatitis 15 .…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, galanin potently modulates neutrophil, NK cell, monocyte and macrophage functions in vitro 8 11 . Furthermore, GAL 3 R is involved in inflammatory diseases in vivo, including experimental arthritis, psoriasis and pancreatitis 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of certain pro- and anti-inflammatory sensory neuropeptides in arthritis models [ 10 , 31 , 50 ], while the overall effect of sensory desensitization was found to be primarily anti-inflammatory and analgesic in our current study. The delayed decrease of MPO-activity has previously also been observed in the K/BxN serum transfer model, where mice deficient in PACAP, a major vasoactive peptide mediator, showed a similarly increased neutrophil ROS production in the late phase of arthritis [ 31 ].…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, it could be possible that GAL also induces tumor-suppressing functions in GAL 3 -R positive GAMs. Regarding immunity and inflammation, we reported recently that GAL 3 -R signaling has both pro-and anti-inflammatory properties (48,52).…”
Section: (Supplementarymentioning
confidence: 99%